Efficiency of Working Capital Management and Firm Value: Evidence From Chinese Listed Firms - Vijayakumaran, R. (International Journal of Financial Research, 2019)
This paper examines the relationship between the efficiency of working capital management (WCM) and the firm value, focusing on a large panel of Chinese listed companies. WCM which involves a trade-off between profitability and risk is a very important element of the financial management of the firm. The net trade cycle (NTC) and its components are used to measure efficiency of WCM, while the firm value is measured by the Tobin’s Q ratio. The study makes use of the panel data methodology to estimate the regression models. This study reports that the net trade cycle is negatively associated with firm value. More specially, the study finds that firm value is adversely affected by the number of days accounts receivable and inventories, indicating that working capital provides a real opportunity for financial executives to release cash and improve firms’ value. The findings of this study are consistent with the idea that managers can enhance firm value by efficiently managing the investment in working capital.
Keywords: working capital management; firm value; Tobin’s Q